IMPLEMENTATION OF TOLERANCE VALUE FOR STUDENTS AT NEW DOLOK SANGGUL HEALTH STIKES - Pardomuan Simanullang; Yonathan Hutagalung; Hizkia Siburian; Hekbron Meha (Fox Justi : Jurnal Ilmu Hukum, 2023)
Indonesia is a large country characterized by its diversity of ethnicities, religions, languages, races, and customs. Throughout Indonesian history, conflicts related to religious, ethnic, and racial issues have occurred. One of the conflicts that has received attention in the mainstream media is inter-religious conflict, such as disputes between Islam as the majority religion and Christianity as a minority religion. To minimize the emergence of prolonged conflicts and their impact on the stability of the Indonesian nation, it is necessary to foster a culture of tolerance among its citizens. An example of a tertiary institution that has successfully implemented the value of tolerance is Baru Dolok Sanggul Health STIKES. What makes it even more unique is that data collection techniques involve interviews, observation, and documentation. Furthermore, the data obtained from the field is processed using the Miles and Huberman model analysis. The results of this study reveal that the implementation of tolerance values for students of Baru Dolok Sanggul Health STIKES includes: (1) understanding, respecting, and appreciating the teachings of each religion to avoid easily getting offended by differences, (2) avoiding conversations that lead to discussions of beliefs, (3) reminding each other to always adhere to the religious practices of each student, (4) providing equal opportunities for each student in terms of classroom learning, student activities, and interactions with other students.